2023
DOI: 10.1038/s42255-023-00847-2
|View full text |Cite
|
Sign up to set email alerts
|

The rs1421085 variant within FTO promotes brown fat thermogenesis

Abstract: One lead risk signal of obesity-rs1421085 T > C within the FTO gene-is reported to be functional in vitro but lack of organismal evidence. Here, we established global and the brown-adipocyte speci c locusknock-in mice to recapitulate this homologous variant in humans and discovered that mice carrying the C-alleles showed increased thermogenic capacity and a resistance to high-fat diet-induced adiposity with enhanced FTO transcription, while FTO knockdown or inhibition effectively eliminated the increased therm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 90 publications
0
3
0
2
Order By: Relevance
“…Obesity research suggests that the FTO gene region alters the function of nearby genes (IRX3 and IRX5), which impact the involvement of fat cells in thermogenesis (Laber et al, 2021;Zhang et al, 2023). The psychiatric literature suggests that this region also affects neuronal activity, namely dopamine receptor type 2 and 3 function (Hess et al, 2013;Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity research suggests that the FTO gene region alters the function of nearby genes (IRX3 and IRX5), which impact the involvement of fat cells in thermogenesis (Laber et al, 2021;Zhang et al, 2023). The psychiatric literature suggests that this region also affects neuronal activity, namely dopamine receptor type 2 and 3 function (Hess et al, 2013;Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…While BMI and alcohol-related GWAS have identified intronic FTO variants (Kranzler et al, 2019; Loos & Yeo, 2014; Zhou et al, 2023), this conjunctional analysis highlights this locus as the region that is most significantly associated with both phenotypes. Obesity research suggests that the FTO gene region alters the function of nearby genes ( IRX3 and IRX5 ), which impact the involvement of fat cells in thermogenesis (Laber et al, 2021; Zhang et al, 2023). The psychiatric literature suggests that this region also affects neuronal activity, namely dopamine receptor type 2 and 3 function (Hess et al, 2013; Zhang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…39 Other model work has suggested that altered thermogenic capacity and resistance to adiposity induced by a high fat diet might explain the genetic associations. 40 Of relevance for this review, these insights highlight how common genetic variant signals are potentially complex in interpretation but have advanced possible pathways relating to variation in levels of adiposity.…”
Section: Genetic Contributions To Obesity: Anchoring Inferencementioning
confidence: 99%
“…Bei einer Ausschaltung von Irx3 nahmen transgene Mäuse unter einer fettreichen Diät kein Gewicht zu [58]. Eine aktuelle Studie konnte diese Effekte auf Irx3 und Irx5 in drei Mausmodellen jedoch nicht einheitlich bestätigen [60]. Diese Studie zeigte, dass die FTO-Variante rs1421085 direkt die Expression von FTO erhöht und Mäuse, die das C-Allel der Variante trugen, weniger Gewicht bei einer fettreichen Diät zunahmen also wildtypische Mäuse [60].…”
Section: Die Polygene Adipositasunclassified
“…Eine aktuelle Studie konnte diese Effekte auf Irx3 und Irx5 in drei Mausmodellen jedoch nicht einheitlich bestätigen [60]. Diese Studie zeigte, dass die FTO-Variante rs1421085 direkt die Expression von FTO erhöht und Mäuse, die das C-Allel der Variante trugen, weniger Gewicht bei einer fettreichen Diät zunahmen also wildtypische Mäuse [60]. Dieser Effekt war jedoch Temperatur-abhängig und bei einer thermoneutralen Temperatur nur abgeschwächt nachweisbar [60].…”
Section: Die Polygene Adipositasunclassified